Reading Ireland : print, reading, and social change in early modern Ireland - Gillespie, Raymond (Politics, culture, and society in early modern Britain., 2005)
This fascinating and innovative study explores the lives of people living in early modern Ireland through the books and printed ephemera which they bought, borrowed or stole from others. While the importance of books and printing in influencing the outlook of early modern people is well known, recent years have seen significant changes in our understanding of how writing and print shaped lives, and was in turn shaped by those who appropriated the written word. This book draws on this literature to shed light on the changes that took place in this unusual European society. The author finds that.